Enzyme replacement therapy in infants and very young children with Gaucher disease using velaglucerase alfa: a single-center experience - Goker-Alpan, Ozlem; Ivanova, Margarita M.; Pathak, Ravi; Wright, Ekaterina (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the effectiveness and safety of enzyme replacement therapy (ERT) with velaglucerase alfa, and offer insights into the clinical course of patients with Gaucher disease (GD) that were diagnosed and treated early in life.Study designA phase IV, observational, retrospective and prospective study (NCT04721366) enrolled children with GD who initiated velaglucerase alfa under 4 years of age. Of twelve patients screened, 11 were enrolled (six boys, five girls; two retrospectively); four were identified through newborn screening (NBS).ResultsMean age of diagnosis was 14 months (range, 2 weeks–38 months) and most patients presented with splenomegaly. Patient genotypes included glucosylceramidase beta 1 gene variants R163X, L444P, R463C, N462K, D409H, 55-bp deletion, and other recombinant alleles. Velaglucerase alfa (60–80 U/kg) was initiated at age ≤3 months (n = 4), >3–≤6 months (n = 2), >6–≤12 months (n = 1), >12–≤18 months (n = 2), and >36–≤48 months (n = 2), administered weekly/every other week, mostly in home settings. Most patients were treated for ≥12 months (range, 2–57 months). Hematological values, organ sizes, and growth parameters improved and/or remained stable for all patients; no typical GD-related bone manifestations were observed. Glucosylsphingosine levels decreased from 90–874 ng/mL to 4–26 ng/mL within 6 months of starting ERT. No drug-related adverse events were recorded.ConclusionsThese preliminary data suggest that velaglucerase alfa is well-tolerated and associated with improvements in clinical parameters in very young children with GD types 1 and 3, offering insights into the early presentation and course of GD in infancy and early childhood.